Reductimetric Determination of Nitrite with Iron(II) in Buffer Medium and in Presence of Oxalate - Vijaya Raju, K. (Asian Journal of Chemistry, 2010)
A simple, convenient and accurate reductimetric titration method has been developed for the determination of nitrite employing iron(II) as a reductant in buffer medium of pH 1.5-2.0 and in presence of 0.06 M sodium oxalate, using methylene blue as a redox indicator. Nitrite in the range of 3.0-12.0 mg has been determined with an accuracy of ± 0.6 % by the method. The precision of the method has been determined by computing the pooled standard deviation and 95 % confidence limits. In this procedure, nitrite ion is reduced to nitric oxide (NO) by iron(II) in one electron reduction step. The redox reaction has been explained based on the formal redox potential of iron system (iron(III)/iron(II) couple) observed in buffer-oxalate medium. The nature of the species expected to be formed between iron(III) and oxalate under the optimum titration conditions of the medium (pH range1.5-2.0 oxalate concentration about 0.06 M) have been proposed using a computer programming known as SIMUL. The interference due to diverse ions has been studied.